2020
DOI: 10.3390/cells9071687
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Parkinson’s Disease: Mechanisms and Therapeutic Implications

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder primarily characterized by the death of dopaminergic neurons that project from the substantia nigra pars compacta. Although the molecular bases for PD development are still little defined, extensive evidence from human samples and animal models support the involvement of inflammation in onset or progression. However, the exact trigger for this response remains unclear. Here, we provide a systematic review of the cellular mediators, i.e., microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
296
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(354 citation statements)
references
References 256 publications
3
296
0
2
Order By: Relevance
“…It is known that neuroinflammation induced by activation of astrocytes and microglia with subsequent dysfunction of endotelhial cells contributes to PD pathogenesis. Besides central inflammation, peripheral proinflammatory profile with altered CD4 + /CD8 + T cells ratios and Treg cells might facilitate neurodegeneration 77 . Several transcriptome studies that were performed in different platforms with different tissues have highlighted the importance of inflammatory pathways in PD pathogenesis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neuroinflammation induced by activation of astrocytes and microglia with subsequent dysfunction of endotelhial cells contributes to PD pathogenesis. Besides central inflammation, peripheral proinflammatory profile with altered CD4 + /CD8 + T cells ratios and Treg cells might facilitate neurodegeneration 77 . Several transcriptome studies that were performed in different platforms with different tissues have highlighted the importance of inflammatory pathways in PD pathogenesis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…169 In addition, aberrant α-Syn is transferred from neurons to microglia and astrocytes, triggering a proinflammatory response. 170,171 α-Syn accumulation by GCase inhibition in mice induces complement C1q 172 expression required for microglial phagocytosis. Intriguingly, genetic Gba1 ablation in dopaminergic mouse neurons activates microglia without neurodegeneration.…”
Section: Cholesterol In Neuroinflammationmentioning
confidence: 99%
“…DLB is caused by the abnormal accumulation of α-syn in neurons, called Lewy bodies (LBs) and Lewy neurites (LNs; Cummings, 2004;Walker et al, 2015). Most DLB cases occur sporadically, but several papers have suggested that DLB has a genetic cause, such as APOE, SNCA, and LRRK2 (Walker et al, 2015;Orme et al, 2018). Excessive accumulation of α-syn in DLB is associated with the loss and dysfunction of dopaminergic neurons and cholinergic neurons (Tiraboschi et al, 2000;Gomperts, 2016).…”
Section: Dlb (Dementia With Lewy Bodies)mentioning
confidence: 99%
“…Many pathological features of PD, such as mitochondrial dysfunction ( Park et al, 2018 ; Wang X.L. et al, 2020 ), neuroinflammation ( Wang et al, 2015 ; Pajares et al, 2020 ), ER stress ( Colla, 2019 ), and impaired protein quality control ( Cook and Petrucelli, 2009 ; Sala et al, 2016 ), can lead to neuronal toxicity. α-Synucleinopathy features the accumulation of aggregated α-syn in neuronal and glial cells ( McCann et al, 2014 ).…”
Section: Neurodegenerative Disorders Associated With α-Synucleinopathmentioning
confidence: 99%